Die jüdische Interpretation der Erprobung Abrahams und ihr Erscheinen im Neuen Testament - KÓKAI-NAGY, Viktor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The Jewish Interpretation of the Trial of Abraham and Its Appearance in the New Testament. In view of the diverse depiction of the events on Mount Moriah in early Jewish literature, it is quite surprising that the story of Isaac’s sacrifice is only clearly recognizable in two texts in the entire New Testament: the Book of Hebrews and the Epistle of James. We will touch upon these two texts at the end of our brief study. The aim of our investigation is to show how the two authors weave the threads from the Hellenistic-Jewish tradition into their own material and further interpret the story of Abraham’s test.